Um estudo sobre a apuração dos lucros cessantes pelo Judiciário paulista - Oliveira Filho, Fernando Viana de (2022)
The present study aims to verify if the judiciary has used the expertise of accountants to evaluate the damage when determining the lost profits. This research analyzes the content of given judgments that have quoted the term 'loss of profits' at the 1st and 2nd Business and Conflict Courts, related to Arbitration of the Central Forum of the Capital, São Paulo, since its opening in December 2017, until April 2021. The present research concluded, as a result of the analysis, that the judiciary does not demonstrate using the technical and scientific ability of accountants, despite the accounting aspect that involves lost profits, which could increase assertiveness